PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM KAMPUNG IKLIM DI DESA GUNUNG MULYA KECAMATAN GUNUNG SAHILAN KABUPATEN KAMPAR - Putri Indrayani; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The Climate Village Program is a national scope program managed by the Ministry of Environment and Forestry in order to increase the involvement of the community and other stakeholders to strengthen the capacity of adaptation to the effects of climate change and reduce greenhouse gas emissions and provide recognition of climate change adaptation and mitigation efforts. has been done that can improve welfare at the local level in accordance with regional conditions. The purpose of this study was to determine community empowerment through the climate village program in the village of Gunung Mulya, Gunung Sahilan Sub-District, Kampar Regency and to know the supporting factors in community empowerment through the climate village program in Gunung Mulya Village, Gunung Sahilan Sub-District, Kampar Regency. This study uses qualitative research using a case study approach and the data needed both primary and secondary data obtained through observation, interviews and documentation and then analyzed based on research problems. The results of this study indicate that: first, community empowerment through the climate village program in the village of Gunung Mulya, Gunung Sahilan Subdistrict, Kampar Regency has been running optimally in accordance with the stages of community empowerment, but there are just a few problems in developing SMEs in business development that have not yet been run. Second, supporting factors in community empowerment through the climate village program in Gunung Mulya Village, Gunung Sahilan Subdistrict, Kampar Regency are motivation and community participation. Keywords : Community Empowerment, Climate Village Program